Chronic Low Back Pain and Sedentary Behavior in Medical College Students - Gaspar LLana, Liliana Elizabeth (2024)
ntroduction: Low back pain is a common condition among medical students, with various risk factors identified. The aim of the study was to evaluate the association between the presence of low back pain in the last 12 months (lbp) and sedentary behavior in medical students at a private university. Materials and Methods: A cross-sectional analytical, prospective observational study was conducted with 167 respondents (101 women and 66 men). The main measurements in this study included sedentary behavior and low back pain in the last 12 months. Sedentary behavior was assessed along with physical activity through the Global Physical Activity Questionnaire (gpaq), while low back pain was measured using the Kuorinka Nordic Musculoskeletal Questionnaire. In addition, demographic and academic variables such as gender, age, and academic cycle of the participants were assessed. Results: A frequency of low back pain of 67.7% and an average sedentary behavior of 9.5 hours (sd = 3.04) were found, 70.1% maintain a healthy level of physical activity. Greater sedentary behavior was found to be associated with a greater presence of lbp. In the multivariate analysis, it was found that for each hour seated, the likelihood of suffering lbp significantly increased (or = 1.17; p = 0.013). Students who remain seated/reclined for 10 or more hours have an increased risk of suffering low back pain (aor = 4.13; p = 0.001) compared to those who spend less than 10 hours in these positions. Conclusion: It is observed that for each hour in a seated/reclined position, the odds ratio of suffering low back pain in students increases by 15%, and accumulating 10 or more hours a day in a seated/reclined position significantly increases the suffering of low back pain in the last 12 months